THE CORRELATION BETWEEN READING MOTIVATION AND READING COMPREHENSION ABILITY OF THE SECOND YEAR STUDENTS’ OF SMA PGRI PEKANBARU - Wahyuni, Tri; Prawati, Atni; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This main objectives of study are to find out; 1) the students’reading motivation, 2) the students’ reading comprehension scores and 3) thecorrelation between reading motivation and reading comprehension ability.The population of the study is 101 students of the second year students, whilethe sample is 34 students are by using the cluster random samplin techniqu wasused in this study. The data were collected through 48 questions about (readingability) student comprehension (Reading Comprehension) and 20 statements(questionnaires) about reading motivation The result of the test was analyzedby using Pearson product moment though SPSS version 23.0. From theanalysis, it was found that the second year students’ of SMA PGRI Pekanbaruwere in the very bad level in their reading motivation, meanwhile the students’reading comprehension mean score 33.38 was in the poor level 38.32. meanscore. The correlation between both variables was in low correlation with thelevel was 0.16. However, building motivation and mindset about having a goodreading motivation is essential to be recommended because it is very useful todevelop students’ English skill and help them to face some tests which correlatewith students’ reading comprehension ability.Keywords: Correlation, Reading Motivation, Reading Comprehension Ability